MENINGKATKAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN AUDIO-VISUAL MATA PELAJARAN IPS PADA SISWA KELAS VII SMP NEGERI 1 RENGEL - Novian, Dimas Dwi; Muaffa, Izzul; Pujiwidada, Hariyanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the use of audio-visual learning media can improve the learning outcomes of seventh grade students at SMP Negeri 1 Rengel, Tuban Regency in social studies subject matter “Past Community Life Activities”. This type of research is a Collaborative Classroom Action Research (PTKK) consisting of two cycles. The approach in this study used a descriptive quantitative approach. The subjects of this study were students of class VII-E which amounted to 32 students. Data collection was carried out by observation and tests which aimed to determine the improvement of student learning outcomes. Data analysis using percentage and descriptive analysis. The results showed that there was an increase in student learning outcomes from cycle I and cycle II, this was indicated by student learning completeness which increased from cycle I by 53% and learning completeness in cycle II by 81%. These results indicate that learning using audio-visual media can improve student learning outcomes in class VII-E.